If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 12b = 8a + 4b Solving 3a + 12b = 8a + 4b Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-8a' to each side of the equation. 3a + -8a + 12b = 8a + -8a + 4b Combine like terms: 3a + -8a = -5a -5a + 12b = 8a + -8a + 4b Combine like terms: 8a + -8a = 0 -5a + 12b = 0 + 4b -5a + 12b = 4b Add '-12b' to each side of the equation. -5a + 12b + -12b = 4b + -12b Combine like terms: 12b + -12b = 0 -5a + 0 = 4b + -12b -5a = 4b + -12b Combine like terms: 4b + -12b = -8b -5a = -8b Divide each side by '-5'. a = 1.6b Simplifying a = 1.6b
| f(3)=x^2-2x+6 | | 130/65 | | (8x+6y-4)+(7x+12y-5)= | | f(x)=x^2-2x+6 | | 1024+x^2=256+x^2 | | 5ln(4x+9)=35 | | 8x-9y-5z=16 | | 4sec^2x+2tan^2x-6=0 | | 7ln(3x+10)=42 | | 4x-5x=8x-9+11x | | 2*(7/2X) | | 3(3-x)=5(2x-7)+2 | | (-2/9)=4/a | | -9-6+3= | | 9(11-k)=9(x-5) | | r(6r+1)=12 | | 1/4x-1/6x=100 | | 59=-75 | | (5a-2b)+(3a-4b)=0 | | 8(w+3)+4=-7w+11 | | 90x+50=100x | | 4(5-x)=-4.9+2.1(6x) | | 5(x+1)-2(x-1)=12 | | -(v+9)+7=-7v-12 | | -15x+8=7-15x | | 9p+7=6+3(p-1) | | x=x^2+6x+15 | | 9q+7=6+3(p-1) | | 3x+7=-2x-23 | | Ln(3)+ln(2)=ln(x) | | -7(s+10)+11=-5s-6 | | 6y+10=4+6y+6 |